Globular-shaped Aβ oligomers have diverse mechanisms for promoting Aβ aggregations with the facilitation of fibril elongation - Hiroto Nakano; Sadao Hikishima; Makoto Mori; Jota Minamikawa; Daiki Muramatsu; Yasuhiro Sakashita; Tokuhei Ikeda; Moeko Noguchi-Shinohara; David B. Teplow; Kenjiro Ono (Neurobiology of Disease)
The accumulation of amyloid β-proteins (Aβ) in the extracellular space, forming insoluble plaques, is a primary pathological process underlying Alzheimer's disease (AD). Among the various Aβ species that appear during Aβ aggregation, Aβ oligomers are considered the most neurotoxic form. However, the precise mechanisms of their molecular functions within the Aβ aggregation cascade have not been clarified so far. This research aimed to uncover the structural and functional characteristics of globular-shaped Aβ oligomers (gAβO) under in vitro conditions. We performed thioflavin T (ThT) assays on low-molecular-weight (LMW) Aβ42, testing different concentrations of Aβ42 mature fibril (MF) seeds and gAβO. Fibril formation was continuously observed using high-speed atomic force microscopy (HS-AFM) in LMW Aβ42 with different sample conditions. Conformational changes of Aβ42 aggregates in the presence of gAβO was also evaluated using circular dichroism spectroscopy. The results of the ThT analysis and HS-AFM observation indicated that gAβO promoted fibril formation of LMW Aβ42 while gAβO itself did not form fibrous aggregates, indicating that gAβO would have a catalytic effects on LMW Aβ42 aggregation. We also showed that the molecular interaction of gAβO was altered by the presence and amount of MF seeds in the reaction buffers, indicating that complex interactions would exist among different Aβ species. The results of our present research demonstrated that gAβO would have significant roles to accelerate Aβ aggregation in AD pathogenesis.225 < 250 words.